Padrão de consumo de alimentos com açúcar de adição entre estudantes de uma instituição pública de ensino superior do sudeste brasileiro - Luciene Rodrigues Reis (2014)
Objective: In the food transition verified in the last century, punctuated by the food industrialization, sugar addition has an important role. This study aimed to estimate the correlation between the frequency of consumption and preference and evaluate the dependence and abuse of industrialized foods containing additional sugar by university students of southeastern Brazil. Method: The investigation instrument was sent by email to all currently enrolled students in presence courses at the educational institution, with orientations about the research and the questionnaire. It consists of the characterization of the sample, including the knowledge of having the disease surveyed; two tables, organized with 21 types of processed foods with additional sugar in its composition that assessed the frequency of consumption and the level of preference of the participants for these foods. The questionnaire to estimate the dependence and abuse of food were based on the MINI Plus, adapted to the additional sugar, and followed the dependence criteria of the DSM-IV. Results: Among the 3665 valid questionnaires, a positive significant correlation between the frequency scales of consumption and enjoyment of foods with additional sugar was observed (r=0,448; p<0.001). The assessment explained 20.7% of the variance in frequency of consumption (R2 = 0.207). The results also demonstrated that 28.6% of students can be considered dependent on these foods and 12.2% abusers. Conclusion: The level of assessment in relation to selected foods had a positive correlation with the ascending frequency of consumption, which is a factor to consider, but not the only one. In relation to dependence and abuse, there is a high association with chronic diseases responsible for serious health problems and high rates of mortality among adults. Therefore, studies on this topic should be encouraged since the results can provide preliminary and promising evidences that dependence on sugar-rich foods can be a common risk factor for developing chronic diseases.